“Inner Engineering” for success—A complementary approach to positive education - Chang, Tracy F. H.; Pundir, Sheetal; Rayapuraju, Akila; Purandare, Pradeep (Frontiers in Education, 2022)
The movement of positive education is growing globally. Positive education aims to balance academic skills with skills of wellbeing. This study introduces the “Inner Engineering” methodology and evaluates its impact on promoting wellbeing and flourishing for college students. Based on the science of yoga, the Inner Engineering methodology comprehensively addresses four major dimensions of human experiences—physiological, cognitive, affective, and energetic experiences and offers methods and processes to optimize wellbeing in all of these dimensions. The study design involves a quasi-experimental one-group with pre- and post-course tests. Participants of the study (n = 92 students) completed both the pre- and post-course surveys. The pair-wise t-test results showed significant improvement in wellbeing (mindfulness, joy, vitality, sleep quality, and health) and flourishing in the academic setting (academic psychological capital, academic engagement, and meaningful studies) and in life (meaningful life) among students who successfully completed the course. These findings suggest that the academic curriculum may be balanced by integrating the yogic sciences of wellbeing which address a more complete spectrum of human experiences as a whole person. This, in turn, has a further effect on flourishing academically and in life. Future studies may involve a larger sample size with a comparison group or a randomized control and a longitudinal follow-up.